2010
DOI: 10.1249/mss.0b013e3181bf24c4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Yoga for African American Heart Failure Patients

Abstract: Yoga therapy offered additional benefits to the standard medical care of predominantly AA HF patients by improving cardiovascular endurance, QoL, inflammatory markers, and flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(157 citation statements)
references
References 31 publications
1
152
1
3
Order By: Relevance
“…[28][29][30][32][33][34][37][38][39][40][41][58][59][60] However, in a meta-analysis, Goyal et al (2014) found that meditation programs were similar in effectiveness to exercise, progressive muscle relaxation, or cognitive-behavioral therapy when compared with inactive controls. 31 In a meta-analysis of mindfulness-based therapies, Khoury et al (2013) found that these treatments were more effective than psychoeducation, supportive therapy, relaxation, and imagery, but they were not more effective than antidepressants or cognitivebehavioral therapy.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…[28][29][30][32][33][34][37][38][39][40][41][58][59][60] However, in a meta-analysis, Goyal et al (2014) found that meditation programs were similar in effectiveness to exercise, progressive muscle relaxation, or cognitive-behavioral therapy when compared with inactive controls. 31 In a meta-analysis of mindfulness-based therapies, Khoury et al (2013) found that these treatments were more effective than psychoeducation, supportive therapy, relaxation, and imagery, but they were not more effective than antidepressants or cognitivebehavioral therapy.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…[54][55][56][57][58]61,64 The remaining studies reviewed the efficacy of interventions based on mindfulness-based interventions, including yoga, meditation, and guided imagery. 51,59,60,62,[64][65][66][67][68][69][70] The studies reviewed here used mindfulness-based interventions in a wide range of high-risk disadvantaged populations, including racial/ethnic minorities, individuals with chronic health conditions (including AIDS and breast cancer), drug and alcohol users, and victims of interpersonal violence and trauma. All of the reviewed studies provided evidence that mindfulness-based interventions are effective in improving physical and mental health, functioning, self-care, and overall quality of life.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…A stressful life, anxiety and depression increase the risk of heart diseases. In this regard, yoga therapy has been found to offer doi: 10.7243/2055-2386-4-11 extra benefits to African American HF patients by improving cardiovascular endurance, quality of life, inflammatory markers, and flexibility [31]. Another study found that relaxation techniques benefitted the quality of life of Chinese patients with chronic HF [32].…”
Section: Risk Factors Of Heart Failurementioning
confidence: 99%